Poverty and Shared Prosperity 2020 : Reversals of Fortune - World Bank (Washington, DC: World Bank, 2020)
Previous Poverty and Shared Prosperity Reports have conveyed the difficult message that the world is not on track to meet the global goal of reducing extreme poverty to 3 percent by 2030. This edition brings the unwelcome news that COVID-19, along with conflict and climate change, has not merely slowed global poverty reduction but reversed it for first time in over twenty years. With COVID-19 predicted to push up to 100 million additional people into extreme poverty in 2020, trends in global poverty rates will be set back at least three years over the next decade. Today, 40 percent of the global poor live in fragile or conflict-affected situations, a share that could reach two-thirds by 2030. Multiple effects of climate change could drive an estimated 65 to 129 million people into poverty in the same period. “Reversing the reversal” will require responding effectively to COVID-19, conflict, and climate change while not losing focus on the challenges that most poor people continue to face most of the time. Though these are distinctive types of challenges, there is much to be learned from the initial response to COVID-19 that has broader implications for development policy and practice, just as decades of addressing more familiar development challenges yield insights that can inform responses to today’s unfamiliar but daunting ones. Solving novel problems requires rapid learning, open cooperation, and strategic coordination by everyone: from political leaders and scientists to practitioners and citizens.